2018
DOI: 10.1002/fsn3.742
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different thermal processing methods on the structure and allergenicity of peanut allergen Ara h 1

Abstract: Boiling and frying can alter the structure of peanut allergens and therefore change the IgE‐binding capacity of the Ara h 1. In this research, we aim to clarify the connections between structural changes and the allergenicity alteration, and recommend an effective thermal method to minimize the allergenicity of Ara h 1. Anion exchange chromatography was used to isolate Ara h 1 from non/heat‐treated peanuts. Ara h 1 in boiled peanuts has a relatively low hydrophobic index, reduced maximum emission wavelength in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 39 publications
(54 reference statements)
2
26
0
Order By: Relevance
“…Atomic force microscopy (AFM) imaging revealed the transformation of spherical proteins into the large rod‐like branched aggregate chain structures in thermally treated peanut that caused a reduction of small molecular weight proteins (Cai, Zhang, Zhu, & Chen, ; O'Konek et al., ). Circular dichroism (CD) spectroscopy and Fourier transform infrared spectroscopy (FT‐IR) studies revealed the collapse of the tertiary structure of peanut allergen proteins caused by unfolding, denaturation, and aggregation when subjected to thermal treatment (Koppelman, Bruijnzeel‐Koomen, Hessing, & de Jongh, ; Rao et al., ; Tian et al., ; Zhang, Zhu et al., ). It was reported that the secondary structure of peanut allergens Ara h 1, 2, and 6 is significantly modified by the application of high‐temperature treatment with a clear reduction in the α‐helices, a slight increase in extended β‐sheet structures, and an increase in the content of irregular coils (Koppelman et al., ; O'Konek et al., ; Rao et al., ; Tian et al., ; Vanga et al., ; Zhang, Zhu et al., ).…”
Section: Effects Of Processing On Peanut Allergens and Immunogenicitymentioning
confidence: 99%
See 2 more Smart Citations
“…Atomic force microscopy (AFM) imaging revealed the transformation of spherical proteins into the large rod‐like branched aggregate chain structures in thermally treated peanut that caused a reduction of small molecular weight proteins (Cai, Zhang, Zhu, & Chen, ; O'Konek et al., ). Circular dichroism (CD) spectroscopy and Fourier transform infrared spectroscopy (FT‐IR) studies revealed the collapse of the tertiary structure of peanut allergen proteins caused by unfolding, denaturation, and aggregation when subjected to thermal treatment (Koppelman, Bruijnzeel‐Koomen, Hessing, & de Jongh, ; Rao et al., ; Tian et al., ; Zhang, Zhu et al., ). It was reported that the secondary structure of peanut allergens Ara h 1, 2, and 6 is significantly modified by the application of high‐temperature treatment with a clear reduction in the α‐helices, a slight increase in extended β‐sheet structures, and an increase in the content of irregular coils (Koppelman et al., ; O'Konek et al., ; Rao et al., ; Tian et al., ; Vanga et al., ; Zhang, Zhu et al., ).…”
Section: Effects Of Processing On Peanut Allergens and Immunogenicitymentioning
confidence: 99%
“…Roasted peanuts have a high resistance for digestion than raw and boiled peanuts, and the roasting of peanut imparts trypsin inhibition activity (Maleki et al., ; Maleki & Hurlburt, ; Petersen et al., ). Roasting also induces the glycation of amino acids (Maillard reaction) that can produce various complex structures of molecules and form intermediate products, which may lead to the formation of new/unidentified allergenics (neo‐allergen; Maleki & Hurlburt, ; Mueller et al., ; Tian et al., ; Verma et al., ; Vissers et al., ).…”
Section: Effects Of Processing On Peanut Allergens and Immunogenicitymentioning
confidence: 99%
See 1 more Smart Citation
“…The method reported by Mondoulet [ 32 ] was used in this part of the experiment. In short, samples were diluted to different concentrations as described earlier [ 33 ]. Protein samples (4 mL) were then mixed with ANS (8 mmol/L, 20 μL) and reacted in the dark for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…According to methods reported by Chen et al(2018) and Tian, Rao, Zhang, Tao, and Xue (2018), western blots was performed as follows: The concentration of protein samples were measured by BCA assay kit (Solarbio Science & Technology Co., Ltd, Beijing, China) according to the manufacturer's instructions. To analysis the immunoreactivity of digested rAra h 1, 10 μg protein were loaded to each well.…”
Section: Western-blottingmentioning
confidence: 99%